Pine Water Horizon - Ziegler, Hannah Noel (Cornfield Review, 2020)
Not only am I️ fond of constructing poetry, but I️ also enjoy taking pictures in my free time. This particular photo was taken at Crater Lake National Park in Chiloquin, Oregon on a very cool June day. The main inspirations for the photograph were the death and rebirth of nature on our beloved earth. The contrasting hues and the grainy depth of the photo still resonate with me today.